(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: The present investigation was carried out to determine concentration of arsenic in milk and dairy products in Can Tho in 2021. Objects and methods: A total of 250 samples of popular commercial milk and dairy products in the study area (based on data reported by the City Food Safety Bureau). In which, 50 powdered milk, 50 raw milk, 50 yogurt, 50 cheese and 50 milk cake samples were collected from farms, individual farmers and dairy shops in Can Tho. It were analysed for determination their Arsenic. Results: Arsenic was detectable in 220/250 samples. The mean concentrations of As in cheese, milk cake, raw milk, yogurt and powdered milk samples were 178,62 µg/L; 169,32 µg/L; 147,44 µg/L; 127,52 µg/L and 106,68 µg/L, respectively. On the other side, this study also reported that the contents of Arsenic in all materials weren’t over the permissible levels of 500 µg/L established by QCVN 8-2:2011/BYT. Conclusion: The use of these products is not affected by Asenic to consumers’ health.